Insights into the mechanism of metal-polymer contact electrification for triboelectric nanogenerator via first-principles investigations. (June 2018) - Wu, Jun; Wang, Xiaoli; Li, Hanqing; Wang, Feng; Yang, Weixu; Hu, Yanqiang
Abstract: Surface micro/nano structures and materials modification are the major methods to enhance the output performance of triboelectric nanogenerator (TENG). However, the microcosmic mechanism on how they take effect has not been clear yet. Herein, the typical material pair Al-PTFE of TENG is taken as the example to study the mechanism of metal-polymer contact electrification via first-principles investigations and provide theoretical basis for the optimized design of TENG. We demonstrate that the interface barrier of the contact materials is the more fundamental parameter related to contact electrification, rather than the effective work function difference which has been thought to be proportional to the amount of charge transfer. The relationship between charge transfer and interface distance is also investigated. We confirm that charge transfer is significantly affected by the stress on the contact region, and it can even occur without contact. Based on the results, we propose that the surface micro/nano structures design on TENG should aim at making the contact regions in an appropriate stress state instead of only increasing the contact area, and improving the specific surface areas in the effective range of contact electrification via nanostructures for generating extra charge transfer freely. In order to provide theoretical basis for surface modification on contact materials which has been little studied, the direction, driving force and the intrinsic cause of charge transfer are investigated. It is demonstrated that the electrons acceptor is the LUMO (lowest unoccupied molecular orbital) on PTFE surface, and the driving force of charge transfer is the electrostatic attraction generated by the electrons acceptor. In addition, the key role and intrinsic mechanism of the interface chemical bond in PTFE is studied. We propose that the fundamental goal of chemical modification on contact materials should be to lower the LUMO energy level on the surface of electron acceptor materials. Graphical abstract: fx1 Highlights: First principle study on the mechanism of Al-PTFE contact electrification is performed. The charge density is significantly affected by the contact stress and the charge transfer can even occur without contact. The electrons acceptor is found to be the LUMO of polymer, which provides direct basis for the materials modification. The chemical bonds of the polymer at the contact interface can significantly improve the charge transfer.